2008
DOI: 10.1159/000131707
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Metabolic Alkalosis, Azotemia and Morbidity in Patients with Chronic Obstructive Pulmonary Disease and Hypercapnia

Abstract: Background: Exacerbation of chronic obstructive pulmonary disease (COPD) is an important cause of morbidity and mortality, but the effect of metabolic compensation of respiratory acidosis (RA) on mortality is not fully understood. Objective: To investigate the relationship between metabolic compensation and mortality in COPD patients with RA. Methods: We prospectively investigated all COPD patients with RA admitted to the respiratory intensive care unit between February 2001 and March 2007. Two hundred and thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 44 publications
3
18
0
Order By: Relevance
“…Ucgun et al reported that development of sufficient metabolic compensation and adequate renal function significantly decreases the mortality rate 22. All these results are similar to results obtained by us.…”
Section: Discussionsupporting
confidence: 87%
“…Ucgun et al reported that development of sufficient metabolic compensation and adequate renal function significantly decreases the mortality rate 22. All these results are similar to results obtained by us.…”
Section: Discussionsupporting
confidence: 87%
“…In patients with hypercapnic respiratory failure due to COPD exacerbation, the presence of a sufficient metabolic compensation and adequate renal function significantly decreases mortality [17]. In our study, the bicarbonate increase overcame the expected renal compensatory response, reflecting a mixed acid-base disorder with metabolic alkalosis due to various causes in patients with multiple comorbidities and undergoing multidrug treatment.…”
Section: Discussionmentioning
confidence: 50%
“…Interestingly, most of the relevant pathophysiological factors also play an important role as predictors of mortality. Furthermore, it has been shown that sufficient metabolic compensation of respiratory acidosis and adequate renal function significantly decrease mortality [41]. …”
Section: Discussionmentioning
confidence: 99%